Історико-правова характеристика статусу суддів та судового розсуду у країнах Стародавнього Сходу - Кравчук, М.; Глабай, А.; Kravchuk, M.; Glabay, A. (СНУ ім. Лесі Українки, 2018)
У статті проведено аналіз статусу суддів та судового розсуду у таких країнах, як Стародавній Єгипет, Стародавня Індія, Стародавній Китай та Стародавній Вавилон. Характерними рисами системи правосуддя у стародавні часи була належність вищої судової влади главі держави (фараону, царю). На місцях судову владу здійснювали призначувані главою держави судді. На судовий розсуд впливали ряд чинників об’єктивного та суб’єктивного характеру. The article analyzes the notions of status of judges and judicial discretion in such countries, as Ancient Egypt, Ancient India, Ancient China and Ancient Babylon. The peculiar feature of the judicial system in ancient times was the fact that the highest judicial power belonged to the Head of a State (Pharaoh, Tsar). At the local level, judicial power was exercised by the judges appointed by the head of a state. A number of objective and subjective factors influenced the judicial discretion. These factors included the social position of both the justice officials and the participants in the process. The ideological (religious) factor had a significant influence on the discretion of the judge in ancient times, although there was a gradual transition from spiritual to secular courts. However, there was one common feature in all the states of the ancient world. It was the requirement regarding the volitional and emotional qualities of a judge. The judge had to be able to hear people and have a high level of the morality norms of the then society.
Historical and Legal Characteristics of the Judges Status and Judicial Discretion in the Countries of the Ancient East
Keywords: Стародавній Схід; статус суддів; судовий розсуд; Ancient East; status of judges; judicial discretion